2011
DOI: 10.1002/sim.4034
|View full text |Cite
|
Sign up to set email alerts
|

Issues of design and statistical analysis in controlled clinical acupuncture trials: an analysis of English‐language reports from Western journals

Abstract: Objective To investigate major methods of design and statistical analysis in controlled clinical acupuncture trials published in the West during the past six years (2003–2009) and, based on this analysis, to provide recommendations that address methodological issues and challenges in clinical acupuncture research. Method PubMed was searched for acupuncture RCTs published in Western journals in English between 2003 and 2009. The keyword used was acupuncture. Results One hundred and eight qualified reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 132 publications
(138 reference statements)
0
11
1
Order By: Relevance
“…Sham intervention ideally should mimic the procedure of acupuncture without eliciting therapeutic effects[48]. However, it has been suggested that sham acupuncture needling also evokes physiological responses that are similar to real acupuncture needling, and this may explain why effect sizes in many sham controlled studies are small[45, 46, 70, 71]. For this reason, some have argued that using non-invasive acupuncture needles as sham control is a better approach than the minimally invasive needling approach we are employing[71, 72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sham intervention ideally should mimic the procedure of acupuncture without eliciting therapeutic effects[48]. However, it has been suggested that sham acupuncture needling also evokes physiological responses that are similar to real acupuncture needling, and this may explain why effect sizes in many sham controlled studies are small[45, 46, 70, 71]. For this reason, some have argued that using non-invasive acupuncture needles as sham control is a better approach than the minimally invasive needling approach we are employing[71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that sham acupuncture needling also evokes physiological responses that are similar to real acupuncture needling, and this may explain why effect sizes in many sham controlled studies are small[45, 46, 70, 71]. For this reason, some have argued that using non-invasive acupuncture needles as sham control is a better approach than the minimally invasive needling approach we are employing[71, 72]. Because of the smaller needle diameter, softer needle body, and very shallow insertion we are employing in this study, we believe the stimulation will be quite minimal, and perhaps even less strong than non-insertive controls that often apply significant surface pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have reported that acupuncture has no significant differencescompared to sham acupuncture [12-14]. To confirm the efficacy of EA for severe chronic functional constipation, we chose a commonly used sham method as described in western journals as the control group - superficial insertion at non-acupuncture points [15] with no current output using an EA simulator. We used an EA apparatus which has the metal wire removed, giving an identical visual appearance to the real one.…”
Section: Discussionmentioning
confidence: 99%
“…5. In addition to a comprehensive and rigorous methodological design, appropriate methods of statistical analysis are also necessary [86,87].…”
Section: Some Suggestions For Acupuncture Trialsmentioning
confidence: 99%